A preparation method of a hydrogen-impermeable perfluorosulfonic acid composite proton exchange membrane for PEM electrolysis of water

CN122918642APending Publication Date: 2026-10-16SHENZHEN GENERAL HYDROGEN ENERGY TECH CORP LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610502664.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-04-16
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

目前,商用质子交换膜以全氟磺酸树脂(PFSA)膜为主,但其在实际应用中存在显著短板:一方面,PFSA 膜在高湿度工况下溶胀率较大,易导致膜结构变形与质子传导通道紊乱;另一方面,长期运行中,阳极产生的自由基会持续侵蚀 PFSA主链,造成膜降解失效;更关键的是,PFSA 膜与催化层、双极板等组件的界面结合易因干湿循环与热应力出现层间分离,严重制约电解槽的稳定性与使用寿命

Benefits of technology

[0015] The beneficial effects of this invention are as follows: This invention achieves synergistic effects through multi-level structural design and material modification. A gradient composite layer is constructed using perfluorosulfonic acid resins with different ion exchange equivalents (EW). Low-EW resin forms efficient proton conduction channels, while high-EW resin provides structural support. Furthermore, the interlayer interfaces form transition zones through molecular chain interpenetration, and SOF polar groups fill microscopic defects, simultaneously optimizing air permeability, water absorption, and swelling rate. A platinum-based composite catalyst modified with a specific process is introduced into the GRC layer. Platinum nanoparticles are highly dispersed on the surface of the composite support, quenching hydroxyl radicals in situ and blocking their oxidative erosion of the PFSA backbone, significantly improving corrosion resistance. The catalyst forms microscopic anchor points on the surface, enhancing the interfacial bonding with the catalyst layer and mitigating the risk of interlayer separation. Step-by-step heat treatment promotes full diffusion and rearrangement of molecular chains, and combined with post-treatment to reconstruct nanochannels, ultimately achieving efficient proton conduction and membrane structure stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918642A_ABST
    Figure CN122918642A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of proton exchange membrane electrolysis of water, and particularly relates to a preparation method of a hydrogen-impermeable perfluorosulfonic acid composite proton exchange membrane for PEM electrolysis of water. The application realizes synergistic effect through multi-level structure design and material modification, adopts perfluorosulfonic acid resins with different ion exchange equivalent weights to construct a gradient composite layer, the low-EW resin forms an efficient proton conduction channel, the high-EW resin provides structural support, and the interfaces between the layers form a transition zone through molecular chain interpenetration, and the S-O-F polar groups fill in micro defects, thereby synchronously optimizing the air permeability, water absorption rate and swelling rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of proton exchange membrane electrolysis technology, specifically relating to a method for preparing a hydrogen perfluorosulfonic acid composite proton exchange membrane for PEM electrolysis. Background Technology

[0002] In proton exchange membrane (PEM) water electrolyzers, the proton exchange membrane, as a core component, plays a crucial role in proton conduction, gas isolation, and catalyst support. Currently, commercially available PEM membranes are mainly perfluorosulfonic acid (PFSA) membranes, but they have significant shortcomings in practical applications: Firstly, PFSA membranes have a large swelling rate under high humidity conditions, which can easily lead to membrane structure deformation and proton conduction channel disorder; secondly, during long-term operation, free radicals generated at the anode continuously erode the PFSA backbone, causing membrane degradation and failure; more critically, the interfacial bonding between the PFSA membrane and components such as the catalyst layer and bipolar plates is prone to interlayer separation due to wet-dry cycles and thermal stress, severely restricting the stability and service life of the electrolyzer.

[0003] To overcome the aforementioned bottlenecks, the Gas Reinforced Conduction Layer (GRC layer) addresses the performance defects of PFSA films through a combination of material improvement, process optimization, and structural innovation. At the material improvement level, a fluoride modifier (platinum black noble metal catalyst) is introduced into the GRC layer substrate framework to form a chemical cross-linked structure with the PFSA film. The high specific surface area of ​​graphite is used to load platinum nanoparticles, effectively blocking the erosion pathways of free radicals on the PFSA film. Summary of the Invention

[0004] The purpose of this section is to outline some aspects of the embodiments of the present invention and to briefly describe some preferred embodiments.

[0005] As one aspect of the present invention, the present invention provides a method for preparing a hydrogen perfluorosulfonic acid composite proton exchange membrane for PEM water electrolysis, comprising, Step 1: Catalyst preparation: Silicon nitride is wetted with alkaline solution and then mixed with platinum black catalyst. The mixture is oxidized and calcined at high temperature in an oxygen-containing atmosphere. After acid leaching and washing, the first catalyst is obtained. Sodium metatungstate, urea, and water were mixed, the pH value was adjusted, and the first catalyst was added. After hydrothermal reaction, the second catalyst was obtained. The second catalyst was heated under a hydrogen-containing atmosphere to obtain the third catalyst; Step 2: Prepare a first perfluorosulfonic acid resin slurry, a second perfluorosulfonic acid resin slurry, and a third perfluorosulfonic acid resin slurry, wherein the third perfluorosulfonic acid resin slurry contains the third catalyst; Step 3: The first perfluorosulfonic acid resin slurry is sequentially coated onto the polyimide base film to form a first resin layer, and the first polytetrafluoroethylene film is bonded together. Then, the first perfluorosulfonic acid resin slurry is coated to form a second resin layer, and the second polytetrafluoroethylene film is bonded together. A first heat preservation treatment is performed. Then, the second perfluorosulfonic acid resin slurry is coated to form a third resin layer, and the third polytetrafluoroethylene film is bonded together. Finally, the third perfluorosulfonic acid resin slurry is coated to form a gas-enhanced conductive layer, thus obtaining a composite film. Step 4: The composite membrane is subjected to a stepped heat preservation treatment in sequence, followed by acid immersion, water washing, and oxidant solution immersion treatment. The polyimide substrate is then removed to obtain the hydrogen permeation-proof perfluorosulfonic acid composite proton exchange membrane.

[0006] As a preferred embodiment of the preparation method described in this invention, step 1 further includes a cleaning pretreatment step: wiping the surfaces of the polyimide substrate and the polytetrafluoroethylene film with an organic solvent, then placing the polytetrafluoroethylene film in a dilute sulfuric acid solution, ultrasonically immersing it under heating conditions, and finally rinsing it with deionized water until neutral.

[0007] As a preferred embodiment of the preparation method described in this invention, in step 2, silicon nitride is soaked in an aqueous sodium hydroxide solution, and then mixed with a platinum black catalyst at a mass ratio of (1-2):1. The mixture is then calcined at 800-900°C for 2-3 hours under an oxygen-containing atmosphere, and then soaked and washed with an aqueous hydrofluoric acid solution to obtain the first catalyst.

[0008] As a preferred embodiment of the preparation method described in this invention, in step 2, the temperature of the hydrothermal reaction is 300-400℃; and the temperature of heating the second catalyst in a hydrogen-containing atmosphere is 250-350℃.

[0009] As a preferred embodiment of the preparation method described in this invention, in step 3, the solid content of the first perfluorosulfonic acid resin slurry is 10-15 wt%, the solid content of the second perfluorosulfonic acid resin slurry is 10-20 wt%, the solid content of the third perfluorosulfonic acid resin slurry is 8-12 wt%, and the content of platinum is 0.2-0.4 wt%.

[0010] In a preferred embodiment of the preparation method described in this invention, in step 3, the ion exchange equivalents of the first perfluorosulfonic acid resin slurry and the second perfluorosulfonic acid resin slurry are different; the ion exchange equivalent of the first perfluorosulfonic acid resin slurry is 700-900, and the ion exchange equivalent of the second perfluorosulfonic acid resin slurry is 1000-1200.

[0011] In a preferred embodiment of the preparation method described in this invention, in step 4, the coating thickness of the first resin layer and the second resin layer is 150-250µm, the coating thickness of the third resin layer is 250-350µm, and the coating thickness of the gas-enhanced conductive layer is 100-200µm.

[0012] As a preferred embodiment of the preparation method described in this invention, in step 4, the temperature of the first heat preservation treatment is 50-70℃, and the heat preservation time is 5-15 minutes.

[0013] As a preferred embodiment of the preparation method described in this invention, step 5, the stepped heat preservation treatment includes: sequentially performing heat preservation at 50-70℃, 80-100℃ and 200-220℃ respectively.

[0014] As a preferred embodiment of the preparation method described in this invention, in step 5, the acid soaking is performed using a 0.2-0.8 mol / L dilute sulfuric acid solution, and the oxidant solution soaking is performed using a 5-15 wt% hydrogen peroxide solution.

[0015] The beneficial effects of this invention are as follows: This invention achieves synergistic effects through multi-level structural design and material modification. A gradient composite layer is constructed using perfluorosulfonic acid resins with different ion exchange equivalents (EW). Low-EW resin forms efficient proton conduction channels, while high-EW resin provides structural support. Furthermore, the interlayer interfaces form transition zones through molecular chain interpenetration, and SOF polar groups fill microscopic defects, simultaneously optimizing air permeability, water absorption, and swelling rate. A platinum-based composite catalyst modified with a specific process is introduced into the GRC layer. Platinum nanoparticles are highly dispersed on the surface of the composite support, quenching hydroxyl radicals in situ and blocking their oxidative erosion of the PFSA backbone, significantly improving corrosion resistance. The catalyst forms microscopic anchor points on the surface, enhancing the interfacial bonding with the catalyst layer and mitigating the risk of interlayer separation. Step-by-step heat treatment promotes full diffusion and rearrangement of molecular chains, and combined with post-treatment to reconstruct nanochannels, ultimately achieving efficient proton conduction and membrane structure stability.

[0016] In the preparation process of this invention, the resin viscosity is moderate, fully impregnating the e-PTFE porous framework to form a continuous and flawless resin-framework interpenetrating structure. This effectively eliminates black spots and gel points caused by resin agglomeration, ensuring membrane homogenization. Functional integration of the GRC layer is achieved: the highly dispersed platinum-based composite catalyst in this layer not only acts as a free radical quencher, blocking the erosion of the PFSA backbone by hydroxyl radicals, but its catalytic activity also promotes the water decomposition reaction kinetics at the interface, allowing the anode catalyst layer to maintain high reactivity even with lower precious metal loadings, thereby reducing the amount of precious metals such as iridium and platinum used. Simultaneously, the GRC layer significantly inhibits hydrogen cross-permeation through the synergistic effect of physical barrier and chemical adsorption. Lifespan improvement: through the three-layer e-PTFE framework constraining swelling, the GRC layer's free radical quenching, and the multi-resin gradient composite eliminating internal stress, these three factors synergistically delay the chemical degradation and mechanical fatigue of the membrane, enabling the PEM electrolyzer to maintain a low voltage decay rate during long-term operation, significantly extending the service life of the perfluorosulfonic acid membrane and membrane electrode assembly. Attached Figure Description

[0017] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below, wherein: Figure 1 This is a schematic diagram of the PFSA proton exchange membrane structure in Example 1. Wherein, 0 is the PI base film, 1 is the resin layer 1, 2 is the first e-PTFE layer, 3 is the resin layer 2, 4 is the second e-PTFE layer, 5 is the resin layer 3, 6 is the third e-PTFE layer, and 7 is the GRC layer.

[0018] Figure 2 For electrochemical performance testing.

[0019] Figure 3 For durability testing. Detailed Implementation

[0020] To make the above-mentioned objectives, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to specific examples.

[0021] Example 1: 1. Cleaning the PI substrate and e-PTFE: Wipe the surface of the PI substrate (Guangboshi) and e-PTFE membrane (thickness approximately 12±3μm, DONALDSON product number / model: 380124E1) with a lint-free cloth soaked in anhydrous ethanol. Immerse in dilute sulfuric acid: Prepare a 0.1 mol / L dilute sulfuric acid solution, immerse the e-PTFE, and ultrasonically soak in a 60℃ constant temperature water bath for 30 min (ultrasonic frequency 20 kHz). After soaking, rinse three times with deionized water until the pH is neutral.

[0022] 2. Preparation of catalysts: 1) Silicon nitride (Si3N4, Maclean) was soaked in 1 mol / L NaOH aqueous solution for 10 min, and then mixed with platinum black catalyst (platinum content of about 97%, purchased from Anhui Masuzu Company) at a mass ratio of 1.5:1. The mixture was then placed at the vent of a high-temperature tube furnace, oxygen was introduced, and the temperature was increased to 850°C at a rate of 5°C / min for high-temperature oxidation calcination and held for 2 hours. After that, it was soaked in 3 mol / L HF aqueous solution for 15 min and washed with deionized water 3-5 times to obtain catalyst 1.

[0023] 2) Mix 1 part sodium metatungstate, 1.25 parts urea, and 2 parts deionized water by mass, adjust the pH to 2 with 1 mol / L hydrochloric acid aqueous solution, add 1 part catalyst 1, stir evenly, put into a high-pressure reactor, heat to 350℃ at a heating rate of 5℃ / min, and keep at the temperature for 5 hours to obtain catalyst 2.

[0024] 3) Place catalyst 2 into the vent of a tube furnace and introduce an H2 / Air (volume ratio 3:7) atmosphere. Heat at 300°C for 2 hours to obtain catalyst 3.

[0025] 3. Preparation of PFSA resin slurry: A resin (solvay, D79) with an ion equivalent (EW) of approximately 720-870 was added to a 70 wt% ethanol aqueous solution. The solid content of the resin solution was 12.5 wt%, and this solution was designated as PFSA resin 1. Take a resin (Cholmous, D2020) with an ion equivalent (EW) of about 1000-1200 and add it to a 65wt% ethanol aqueous solution. The solid content of the resin solution is 15wt%, and it is denoted as PFSA resin 2.

[0026] A resin (Cholmous, D2020) with an ion equivalent (EW) of approximately 1000-1200 was added to a 60wt% ethanol aqueous solution, resulting in a resin solution with a solid content of 10.5wt%. Catalyst 3 was added to make the platinum content in the solution 0.25wt%, and this solution was designated as PFSA resin 3.

[0027] 4. Preparation of PFSA proton exchange membrane: Take a PI base film (polyimide film, Guangboshi), coat it with PFSA resin 1 with a thickness of 200 µm, denoted as resin layer 1; attach an e-PTFE film (first e-PTFE layer) onto resin layer 1, then continue coating the e-PTFE film with PFSA resin 1 with a thickness of 200 µm, denoted as resin layer 2; attach an e-PTFE film (second e-PTFE layer) onto resin layer 2; heat at 60℃ for 10 min, then continue coating with PFSA resin 2 with a thickness of 300 µm, denoted as resin layer 3; attach an e-PTFE film (third e-PTFE layer) onto resin layer 3, then continue coating with PFSA resin 3 with a thickness of 150 µm as GRC layer; heat the resulting PFSA film at 60℃ for 10 min, at 90℃ for 30 min, and finally at 210℃ for 10 min; then immerse the resulting PFSA film in 0.5 The membrane was soaked in a mol / L dilute sulfuric acid solution at room temperature for 1 h, washed with deionized water, and then soaked in 10 wt% H2O2 at room temperature for 5 min to complete the reconstruction of the nanochannels and achieve efficient transport of water vapor and protons. The PI substrate was then removed to obtain a PFSA proton exchange membrane with a thickness of 80 ± 5 µm.

[0028] Comparative Example 1: The difference between the preparation process of the PFSA proton exchange membrane and Example 1 is that: resin (Cholmous, D2020) with an ion equivalent (EW) of approximately 1000-1200 is added to a 60wt% ethanol aqueous solution, the solid content of the resin solution is 10.5wt%, and platinum black catalyst is added to make the platinum content in the solution 0.25wt%. The rest of the preparation method is the same as in Example 1.

[0029] Comparative Example 2: The difference between the preparation process of the PFSA proton exchange membrane and Example 1 is that: resin (Cholmous, D2020) with an ion equivalent of about 1000-1200 EW is added to a 60wt% ethanol aqueous solution, the solid content of the resin solution is 10.5wt%, and catalyst 1 is added to make the platinum content in the solution 0.25wt%. The rest of the preparation method is the same as in Example 1.

[0030] Comparative Example 3: The difference between the preparation process of the PFSA proton exchange membrane and Example 1 is that: resin (Cholmous, D2020) with an ion equivalent of about 1000-1200 EW is added to a 60wt% ethanol aqueous solution, the solid content of the resin solution is 10.5wt%, and catalyst 2 is added to make the platinum content in the solution 0.25wt%. The rest of the preparation method is the same as in Example 1.

[0031] Comparative Example 4: The preparation process of the PFSA proton exchange membrane differs from that in Example 1 as follows: A PI base membrane (polyimide membrane, Guangboshi) is taken, and a 200 µm thick layer of PFSA resin 1 is coated onto it, designated as resin layer 1. An e-PTFE membrane is then bonded onto resin layer 1, followed by another 200 µm thick layer of PFSA resin 1 coated onto the e-PTFE membrane, designated as resin layer 2. The e-PTFE membrane is then bonded onto resin layer 2. The membrane is kept at 60°C for 10 min, and a 300 µm thick layer of PFSA resin 1 is coated onto it, designated as resin layer 3. The e-PTFE membrane is then bonded onto resin layer 3, and a 150 µm thick layer of PFSA resin 3 is coated onto it as a GRC layer. The resulting PFSA membrane is then kept at 60°C for 10 min, 90°C for 30 min, and finally 210°C for 10 min. Afterward, the resulting PFSA membrane is immersed in 0.5... The PI substrate was soaked in a mol / L dilute sulfuric acid solution at room temperature for 1 hour, washed with deionized water, and then soaked in 10wt% H2O2 at room temperature for 5 minutes before removing the PI substrate. The remaining preparation methods were the same as in Example 1.

[0032] Comparative Example 5: The preparation process of the PFSA proton exchange membrane differs from that in Example 1 in the following ways: A PI substrate membrane (polyimide membrane, Guangboshi) is taken, and a 200 µm thick layer of PFSA resin 1 is coated onto it, designated as resin layer 1. An e-PTFE membrane is then bonded onto resin layer 1, followed by another 200 µm thick layer of PFSA resin 1 coated onto the e-PTFE membrane, designated as resin layer 2. The e-PTFE membrane is then bonded onto resin layer 2. The membrane is heated to 60°C for 10 min, and then a 300 µm thick layer of PFSA resin 2 is coated onto it, designated as resin layer 3. The e-PTFE membrane is then bonded onto resin layer 3, and a 150 µm thick layer of PFSA resin 3 is coated onto it as a GRC layer. The resulting PFSA membrane is then heated to 60°C for 10 min, 90°C for 30 min, and finally 210°C for 10 min. Afterwards, it is washed with deionized water to remove the PI substrate membrane, yielding the PFSA proton exchange membrane. The remaining preparation methods are the same as in Example 1.

[0033] Comparative Example 6: The difference between the preparation process of the PFSA proton exchange membrane and Example 1 is that: resin (Cholmous, D2020) with an ion equivalent (EW) of approximately 1000-1200 is added to a 60wt% ethanol aqueous solution, the solid content of the resin solution is 10.5wt%, and catalyst 3 is added to make the platinum content in the solution 1wt%. The rest of the preparation method is the same as in Example 1.

[0034] Proton conductivity testing: The four-electrode AC impedance method as specified in GB / T 45332-2025 and GB / T 20042.3-2022 was used. The proton exchange membrane to be tested was cut into 20 mm × 20 mm square samples, and three tests were performed, with the average value taken. The samples were ultrasonically cleaned in deionized water for 10 min, then immersed in 0.5 mol / L H₂SO₄ solution at 80 ℃ for 10-30 min for proton activation. The samples were repeatedly rinsed with deionized water until the pH of the rinsing solution was > 6.0, and then vacuum dried at 80 ℃ for 4 h. The dried samples were then equilibrated in a test chamber at 50 ℃ and 100% relative humidity for 30 min. AC impedance spectroscopy was performed using an electrochemical workstation, with a frequency range of 1 * 10⁵ Hz - 0.1 Hz and an AC amplitude of 5 mV. The results were obtained from the membrane resistance R, electrode spacing L, sample width W, and sample thickness d. The proton conductivity is calculated using the formula σ = L / (R×W×d), with units of mS / cm.

[0035] Gas permeability (hydrogen permeability) test: The test was conducted according to the pressure difference method specified in GB / T 45332-2025 and GB / T 20042.3-2022. The proton exchange membrane to be tested was prepared into a square sample with an effective permeation area of ​​5*5 cm², and three sets of tests were performed, with the average value taken. The sample was ultrasonically cleaned in deionized water for 10 min, dried in an oven at 80 ℃ for 4 h, and then equilibrated at 23℃±2 ℃ and 50% RH±5% RH for 60 min. The sample was placed in a gas permeation cell and sealed. After vacuuming until the baseline stabilized, a constant pressure difference was established across the membrane. The test temperature was maintained at 23 ℃±2 ℃, and the hydrogen pressure change curve on the low-pressure side over time was recorded. After the permeation reached steady state, the hydrogen permeability was calculated based on the pressure rise rate, with units of cm³ / (m²·d·Pa).

[0036] Tensile strength test: The test was conducted according to GB / T 45332-2025, GB / T 20042.3-2022 and GB / T 1040.1-2018. The specimens were dumbbell-shaped, with a total length of 70 mm, a gauge length of 25 mm, a gauge width of 4 mm, and an end width of 10 mm. Three specimens were taken from each longitudinal and transverse direction. The specimens were ultrasonically cleaned with deionized water for 30 min, activated with 0.5 mol / L H2SO4 solution at 80 ℃ for 60 min, rinsed with deionized water, and vacuum dried at 80 ℃ for 60 min. The specimens were conditioned in a standard environment of 23℃±2 ℃ and 50% RH±5% RH for ≥12 h. The specimens were then clamped in a universal tensile testing machine and stretched at a rate of 50 mm / min until fracture, and the maximum breaking force F was recorded. The gauge width w and thickness t were measured. The tensile strength is calculated using the formula σt = F / (w×t), with units of MPa; the arithmetic mean of parallel specimens is taken as the final result.

[0037] Transmittance test: Transmittance was determined according to GB / T 2410-2008. The sample was cut into a 50 mm × 50 mm square and conditioned for 4 h at 23 ℃ ± 2 ℃ and 50 %RH ± 5 %RH. After calibrating the baseline using a transmittance meter, the visible light transmittance of the sample was tested. The results are expressed as a percentage (%). Each group of parallel samples consisted of 3 pieces, and the arithmetic mean was taken.

[0038] Swelling rate test: The swelling rate was determined according to GB / T 20042.3-2022. The sample was cut into a 20 mm × 20 mm square, dried under vacuum at 80 ℃ to constant weight, and the dry size was measured. The sample was then immersed in deionized water at 80 ℃ for 24 h, removed, and the surface moisture was absorbed before measuring the wet size. The dimensional change rate was calculated, and the result was expressed as a percentage (%). Each group consisted of 3 parallel samples, and the arithmetic mean was taken.

[0039] The test results are shown in Tables 1-2.

[0040] Table 1

[0041] Table 2

[0042] Electrochemical performance testing: IV performance and electrochemical lifetime testing were conducted by assembling the membrane electrode assembly. A catalyst-coated membrane (CCM) was assembled between a 0.4 mm thick titanium felt anode, a 0.24 mm thick gas diffusion layer (GDL) cathode, and two PTFE gaskets to form a membrane electrode assembly (MEA). The effective electrode area was 25 cm². 2 The platinum loading of the CL anode is 1.0 mgIr / cm. 2 The platinum loading of the cathode CL is 0.4 mgPt / cm². 2 A 140µm thick gasket was selected for the anode, and a 100µm thick gasket for the cathode. The hardware was tightened to a torque of 8 Nm. The system was tested at 65℃ and a circulating water flow rate of 100 mL / min with a torque of 0 A / cm. 2 -0.5 A / cm 2 -1 A / cm 2 -2 A / cm 2 After activation for 15 minutes, at 2 A / cm 2 Chemical lifetime tests were conducted at a current density exceeding 1000 hours to determine voltage change trends and calculate the performance degradation rate of the CCM.

[0043] IV performance testing was conducted at 65℃ with a circulating water flow rate of 100 mL / min, and a test step size of 0.5 A / cm. 2 Perform the test and record 0 A / cm 2 -1 A / cm 2 -2 A / cm 2 -3 A / cm 2 Corresponding voltage data. All tests were conducted on a PEM water electrolysis test bench.

[0044] Electrochemical impedance spectroscopy (EIS) was used to monitor changes in the adhesion between membrane modules. The electrochemical workstation was connected to the corresponding anode and cathode of the single cell, and the EIS mode was selected, with the frequency set to 0.1–10 Hz. 5 HZ. See Figure 2 .

[0045] For durability testing, the sample from Example 1 was tested at 65°C with a circulating water flow rate of 100 mL / min and a test current of 2 A / cm. 2 The corresponding data from the durability tests are as follows. All tests were conducted on a PEM water electrolysis test bench. See [link / reference]. Figure 3 .

[0046] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A method for preparing a hydrogen-proof perfluorosulfonic acid composite proton exchange membrane for PEM water electrolysis, characterized in that, include, Step 1: Catalyst preparation: Silicon nitride is wetted with alkaline solution and then mixed with platinum black catalyst. The mixture is oxidized and calcined at high temperature in an oxygen-containing atmosphere. After acid leaching and washing, the first catalyst is obtained. Sodium metatungstate, urea, and water were mixed, the pH value was adjusted, and the first catalyst was added. After hydrothermal reaction, the second catalyst was obtained. The second catalyst was heated under a hydrogen-containing atmosphere to obtain the third catalyst; Step 2: Prepare a first perfluorosulfonic acid resin slurry, a second perfluorosulfonic acid resin slurry, and a third perfluorosulfonic acid resin slurry, wherein the third perfluorosulfonic acid resin slurry contains the third catalyst; Step 3: The first perfluorosulfonic acid resin slurry is sequentially coated onto the polyimide base film to form a first resin layer, and the first polytetrafluoroethylene film is bonded together. Then, the first perfluorosulfonic acid resin slurry is coated to form a second resin layer, and the second polytetrafluoroethylene film is bonded together. A first heat preservation treatment is performed. Then, the second perfluorosulfonic acid resin slurry is coated to form a third resin layer, and the third polytetrafluoroethylene film is bonded together. Finally, the third perfluorosulfonic acid resin slurry is coated to form a gas-enhanced conductive layer, thus obtaining a composite film. Step 4: The composite membrane is subjected to a stepped heat preservation treatment in sequence, followed by acid immersion, water washing, and oxidant solution immersion treatment. The polyimide substrate is then removed to obtain the hydrogen permeation-proof perfluorosulfonic acid composite proton exchange membrane.

2. The preparation method according to claim 1, characterized in that, Step 1 also includes a cleaning pretreatment step: wiping the surfaces of the polyimide substrate and the polytetrafluoroethylene film with an organic solvent, then placing the polytetrafluoroethylene film in a dilute sulfuric acid solution, ultrasonically immersing it under heating conditions, and finally rinsing it with deionized water until neutral.

3. The preparation method according to claim 1 or 2, characterized in that, In step 2, silicon nitride is soaked in an aqueous sodium hydroxide solution, then mixed with platinum black catalyst at a mass ratio of (1-2):1, calcined at 800-900℃ for 2-3 hours in an oxygen-containing atmosphere, and then soaked and washed with hydrofluoric acid aqueous solution to obtain the first catalyst.

4. The preparation method according to claim 1 or 2, characterized in that, In step 2, the hydrothermal reaction temperature is 300-400℃; the temperature at which the second catalyst is heated in a hydrogen-containing atmosphere is 250-350℃.

5. The preparation method according to claim 1 or 2, characterized in that, In step 3, the solid content of the first perfluorosulfonic acid resin slurry is 10-15wt%, the solid content of the second perfluorosulfonic acid resin slurry is 10-20wt%, the solid content of the third perfluorosulfonic acid resin slurry is 8-12wt%, and the content of platinum is 0.2-0.4wt%.

6. The preparation method according to claim 1 or 2, characterized in that, In step 3, the ion exchange equivalents of the first perfluorosulfonic acid resin slurry and the second perfluorosulfonic acid resin slurry are different; the ion exchange equivalent of the first perfluorosulfonic acid resin slurry is 700-900, and the ion exchange equivalent of the second perfluorosulfonic acid resin slurry is 1000-1200.

7. The preparation method according to claim 1 or 2, characterized in that, In step 4, the coating thickness of the first resin layer and the second resin layer is 150-250µm, the coating thickness of the third resin layer is 250-350µm, and the coating thickness of the gas-enhanced conductive layer is 100-200µm.

8. The preparation method according to claim 1 or 2, characterized in that, In step 4, the temperature of the first heat preservation treatment is 50-70℃, and the heat preservation time is 5-15 minutes.

9. The preparation method according to claim 1 or 2, characterized in that, In step 5, the stepped insulation treatment includes: sequentially performing insulation at 50-70℃, 80-100℃, and 200-220℃.

10. The preparation method according to claim 1 or 2, characterized in that, In step 5, the acid soaking is performed using a 0.2-0.8 mol / L dilute sulfuric acid solution, and the oxidant solution soaking is performed using a 5-15 wt% hydrogen peroxide solution.